Functional significance of phylogeographic structure in a toxic benthic marine microbial eukaryote over a latitudinal gradient along the East Australian Current. Issue 13 (21st May 2020) - Verma, Arjun; Hughes, David J.; Harwood, D. Tim; Suggett, David J.; Ralph, Peter J.; Murray, Shauna A.
Abstract: Genetic diversity in marine microbial eukaryotic populations (protists) drives their ecological success by enabling diverse phenotypes to respond rapidly to changing environmental conditions. Despite enormous population sizes and lack of barriers to gene flow, genetic differentiation that is associated with geographic distance, currents, and environmental gradients has been reported from planktonic protists. However, for benthic protists, which have reduced dispersal opportunities, phylogeography and its phenotypic significance are little known. In recent years, the East Australian Current (EAC) has intensified its southward flow, associated with the tropicalization of temperate waters. Benthic harmful algal species have been increasingly found in south‐eastern Australia. Yet little is known about the potential of these species to adapt or extend their range in relation to changing conditions. Here, we examine genetic diversity and functional niche divergence in a toxic benthic dinoflagellate, Ostreopsis cf. siamensis, along a 1, 500 km north–south gradient in southeastern Australia. Sixty‐eight strains were established from eight sampling sites. The study revealed long‐standing genetic diversity among strains established from the northern‐most sites, along with large phenotypic variation in observed physiological traits such as growth rates, cell volume, production of palytoxin‐like compounds, and photophysiological parameters. Strains from the southern populations were more uniform in both genetic and functional traits, and have possibly colonized their habitats more recently. Our study reports significant genetic and functional trait variability in a benthic harmful algal species, indicative of high adaptability, and a possible climate‐driven range extension. The observed high trait variation may facilitate development of harmful algal blooms under dynamic coastal environmental conditions. Abstract : Genetic diversity and phenotypic diversity in marine microbial eukaryotic populations are critical for adaptability, range expansion, and potential bloom formation. In this study, we report significant functional trait variability in a benthic harmful algal species, indicative of high adaptability, and a possible climate‐driven range extension along the East Australian Current region in the South Pacific. The observed high trait variation may facilitate development of harmful algal blooms under dynamic coastal environmental conditions.